Matching Heat Pump Configurations and Process Parameters for Cost‐Minimal Heat‐Integrated CO2-Capturing Process - Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
ABSTRACT The integration of heat pumps offers a promising route for electrifying chemical processes and reducing CO 2 emissions. Their feasibility strongly depends on the temperature levels and the quantities of available heat sources and sinks, which can be influenced by adjusting process operating parameters to enhance integration potential. The number and quality of these sources and sinks also determine suitable heat pump configurations and therefore the technical and economic viability of implementation. In addition, refrigerant selection is a critical factor, as it is restricted by regulations such as the F‐Gas Regulation. This study investigates how different operating parameters affect the integration potential of various heat pump configurations in a CO 2 absorption process using MEA as solvent. Furthermore, economic evaluations are carried out considering different electricity price scenarios and allowable refrigerants.

Frequency Synthesis Based on MLLs - Bahmanian, Meysam; Scheytt, J. Christoph (Springer Series in Optical Sciences)
Abstract In this chapter, the precision of optical clocks based on mode-locked laser (MLL) is compared with more conventional types of clock sources. It is shown that the phase noise of the optical pulse train from the MLL can be better than other types of clock sources by orders of magnitude. Then, an abstract representation of frequency synthesizer is demonstrated. Different techniques for RF generation using MLL are shown, and their pros and cons are discussed. Finally, a comparison of all these techniques is made with respect to their phase noise and capability to generate RF signal with different frequencies for different applications.

Knowledge Gaps in Circular Product Development: A Systematic Literature Review of the Manufacturing Industry - Twardzik, Jan Luca; Humpert, Lynn; Cichon, Gerrit; Dumitrescu, Roman (Lecture Notes in Mechanical Engineering)

Historisches Lernen - Meyer-Hamme, Johannes; Hartung, Olaf (Handbuch Praxis des Geschichtsunterrichts)

Flexible operation strategies for heat pumps in district heating systems using dynamic electricity prices - Rahlf, Henning Christoph; Divkovic, Denis; Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Energy Conversion and Management)
Electrifying the heating sector is essential for achieving global climate targets like the Paris Agreement’s 1.5 °C goal. In Germany, where 80 % of household energy goes to space heating and hot water, shifting to low-carbon solutions is crucial. Fossil-fuelled district heating networks can incorporate renewable energy via heat pumps, improving efficiency. Although heat pump design typically favours minimal temperature lifts, higher lifts can be economically viable with low electricity prices and abundant renewables. Adding thermal energy storage boosts operational flexibility. This study explores a flexible heat pump operation incorporating part load behaviour with a thermal energy storage in a German city’s district heating system to minimise costs and carbon dioxide emissions. Using a mixed-integer linear programming model, it examines the impact of temperature adjustments and storage on system efficiency. The results show that the integration of a heat pump in a district heating system reduces operating costs. Compared to a supply without a heat pump, with levelised cost of heating of 9.98 cent/kWhth and a fixed operating mode with costs between 9.96 cent/kWhth and 11.49 cent/kWhth, the flexible use results in lowest costs of 9.85 cent/kWhth, while also reducing overall CO2 emissions. Using a full factorial sensitivity analysis, the levelised cost of heating ranged between 9.15 cent/kWhth in the best case and 10.37 cent/kWhth in the worst case for the selected configuration.
Keywords: Heat transition; Optimisation; Temperature flexibility; Decarbonisation; Multi energy

Analysis of bidirectional EV charging infrastructures within industrial DC grids - Rahlf, Henning Christoph; Knorr, Lukas; Althoff, Simon; Meschede, Henning (Smart Energy)
Industrial electrification is increasing to reduce fossil fuel dependence, alongside a growing share of volatile renewables. A secure and reliable energy supply is crucial for industry, leading to a shift from centralised to decentralised grid structures. DC microgrids becoming increasingly popular in industry, since they enable energy recuperation from braking, reduce components and cables, and integrate storage and local generation to manage supply interruptions or peak loads. EVs add further synergies by serving as mobile storage units, helping to store and redistribute locally generated renewable energy. This paper analyses how EV integration in droop-controlled DC grids can contribute to a more stable, low-emission and peak-reduced load profile to the supply grid through load shifting and bridge interruptions. A droop-controlled DC grid model has been developed, incorporating an EV charging park based on probability functions. Scalable scenarios allow for diverse condition analysis using an energy management system that utilises fuzzy logic and sequential MILP optimisation. It has been shown that a 7% improvement of coefficient represented grid-serving behaviour is possible by load shifting. It has also been demonstrated that an optimised EMS can reduce the demand-based CO2 emissions by 41kg for a representative day compared to a fuzzy logic EMS. At the same time peak load is decreased yielding a more constant residual load. These results highlight the potential of a controlled bidirectional charging infrastructure in DC grids and underscore the need to explicitly consider charging processes to ensure a residual load as constant as possible.
Keywords: DC-grid; Droop control; Grid-serving behaviour; Grid stability; Bidirectional charging; Sequential decision; MILP optimisation

Temporary Fix Or Process Innovation? A Fuzzy-Set Qualitative Comparative Analysis Of Workarounds - Hellweg, Talea Davina; Sandfort, Luc Dana; Reineke, Malte Fabian; Bartelheimer, Christian; Beverungen, Daniel (European Conference on Information Systems (ECIS) 2026 Proceedings)

Foreign Language Professional Communicative Competence as a Component of Language Teachers’ Professional Competence (n.d.). - Bürgel, Christoph; Mertens, Jürgen (Manual of Pedagogical Linguistics)

Portfolio im Kontext von Mehrsprachigkeit - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Erst-, Zweit- und Mehrsprachenerwerb - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Fisheries and Fishing - Sackel, Johanna (The Routledge Handbook on the Economic History of Natural Resources)

Design Science Research in an Era of Generative AI—Challenges and Theoretical Guidelines - zur Heiden, Philipp; Beverungen, Daniel; Bartelheimer, Christian; Breidbach, Christoph (Lecture Notes in Computer Science)
Information systems (IS) research is increasingly exploring the potential of generative artificial intelligence (GenAI), such as large language models (LLMs). For design science research (DSR), such technologies foster entirely new vistas for the design of IT artifacts that make use of their generative capabilities, but also influence DSR methodology. This shift is much more profound than it has been discussed so far. To identify existing implications of GenAI for design-oriented research in IS, we report results from an integrative literature review of recent DSR publications in leading IS outlets. Thereby, we synthesize five major theoretical challenges that arise when using GenAI in DSR projects: (1) an obscure composition of the artifact, (2) an opaque contextualization of the LLM, (3) a fragile internal consistency of the artifact, (4) a rapid erosion of prescriptive knowledge, and (5) missing methodological guidance. We investigate these challenges and conceptualize a set of three guidelines that inform DSR in the rising era of GenAI. These guidelines support researchers in designing and justifying GenAI-related DSR processes and in precisely articulating the theoretical grounding of their design decisions and evaluation strategies.

Modellieren und Denken im Diskontinuum - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Zeitschrift für Didaktik der Naturwissenschaften)

ChoraleWind: An Expressive Wind-Quartet Dataset for End-to-End Rendering from the Neues Thüringer Choralbuch - Axel, Axel; Aida, Aida; Manuel, Manuel; Meinard, Meinard; Stefan, Stefan (Proc. of the International Computer Music Conference (ICMC))

Methoden und Perspektiven digitaler Edition von Choralbüchern - Berndt, Axel; Münzmay, Andreas; Amiryan-Stein, Aida (Telemann als interdisziplinärer Forschungsgegenstand: Internationale Wissenschaftliche Konferenz)

Musical Instrument Directivity Modelling and Applications to Virtual Acoustics - Mauro, Davide Andrea; Berndt, Axel (DAGA 2026 – 52nd Annual Meeting on Acoustics)

Material Transition by Friction Induced and Continuous Solid-State Recycling of Aluminum Scrap - Gabsa, Steffen; Homberg, Werner (Key Engineering Materials)
The utilisation of friction-induced solid-state recycling, methodically adapted to the CoNform process, facilitates the continuous production of semi-finished products. The material intended for recycling is conveyed continuously via a rotating wheel. The volume flow is influenced by fixed surfaces, deflections, and constrictions, thereby creating an asymmetrical flow profile. In order to effect a change in the mechanical properties of the semi-finished product, the material fed into the process can be modified. This enables the amalgamation of two alloys or the direct transition between them. The inhomogeneous flow conditions present within the tool give rise to the mixing of materials, thereby creating a graded multi-material zone. The multi-material zone was divided into different areas and traced back to the process conditions. Within the transitions, the connections between the alloys were examined, as well as the influence on the boundary layer. Material properties were determined for the individual areas and located along the length of the profile.

How are gaze aversions and mutual gaze related to the topical development of dyadic explanatory interactions? - Lazarov, Stefan Teodorov; Grimminger, Angela (Journal of Nonverbal Behavior)
Abstract Gaze behavior, being continuously accessible to interlocutors in face-to-face interactions, serves as a cue for managing turn-taking, regulating the duration of topical sequences, and supporting cognitive processing in various everyday conversational contexts. The present study seeks to enhance the understanding of the relation between two forms of interactive gaze behavior – gaze aversions and mutual gaze – and the topical development in the explanatory discourse. To do so, we analyzed 24 dyadic board game explanations in which one explainer subsequently explained a board game to three different explainees while the board game was physically absent from the shared space. The main objective of the present study was to investigate the relation of gaze aversions and mutual gaze to the topical development of explanations. For this, based on previous research (Lazarov et al., 2024; Rossano, 2012) we hypothesized that (1) gaze aversions are more likely to be associated with topic changes than topic continuations, and that (2) mutual gaze is more likely to be associated with topic continuations than topic changes. In addition, we explored how the two forms of gaze behavior are related to the interlocutor who initiates a topic change or continuation. Our proportional analysis using a Generalized linear mixed effects model revealed that gaze aversions are related to topic changes initiated by both interlocutors. In contrast, the analysis did not reveal a significant relation between mutual gaze and topic continuations, which could be explained by the feedback elicitation function of mutual gaze at the end of speakers’ utterances (Bavelas et al., 2002; Brône et al., 2017; Kendon, 1967) while monitoring the addressees’ understanding (Clark & Krych, 2004) and the complexity of the analyzed fixed and random effects.

Numerical approaches to entangling dynamics from variational principles - Offen, Christian; Wembe Moafo, Boris Edgar; Ares, Laura; Sperling, Jan; Ober-Blöbaum, Sina (Journal of Physics A: Mathematical and Theoretical)
Abstract In this work, we address the numerical identification of entanglement in dynamical scenarios. To this end, we consider different programs based on the restriction of the evolution to the set of separable (i.e., non-entangled) states, together with the discretization of the space of variables for numerical computations. As a first approach, we apply linear splitting methods to the restricted, continuous equations of motion derived from variational principles. We utilize an exchange interaction Hamiltonian to confirm that the numerical and analytical solutions coincide in the limit of small time steps. The application to different Hamiltonians shows the wide applicability of the method to detect dynamical entanglement. To avoid the derivation of analytical solutions for complex dynamics, we consider variational, numerical integration schemes, introducing a variational discretization for Lagrangians linear in velocities. Here, we examine and compare two approaches: one in which the system is discretized before the restriction is applied, and another in which the restriction precedes the discretization. We find that the ‘first-discretize-then-restrict’ method becomes numerically unstable, already for the example of an exchange-interaction Hamiltonian, which can be an important consideration for the numerical analysis of constrained quantum dynamics. Thereby, broadly applicable numerical tools, including their limitations, for studying entanglement over time are established for assessing the entangling power of processes that are used in quantum information theory.

The Futures of Digital Democracy: Four Scenarios - Fuchs, Christian; Museba, Joel; Friesch, Kevin (Open Research Europe)
This paper investigates the potential impacts of digitalisation on society and democratic governance through the construction of four realist science fiction scenarios. The study aims to delineate desirable and undesirable digital futures to inform policy discourse and strategic planning. It begins with the outlining of the research basis and methodology, where it employs a methodological synthesis of the Scenario Development Technique from the UN Strategic Foresight Guide and STEEP Analysis. This approach integrates a macro environmental assessment of socio-cultural, technological, economic, environmental, and political dimensions to identify key drivers of change and differences. These are then mapped onto a two-by-two matrix defined by two primary axes. This combination enabled the development of four scenarios examining the impact of digital technologies across these dimensions. The scenarios diverge along two axes. The vertical axis represents the mode of societal organisation and political power (authoritarianism versus democracy). The horizontal axis represents the mode of governance and citizen engagement (representation versus participation). By contrasting these divergent paths, this paper provides a critical framework for analysing how digital technologies intersect with political will and socioeconomic structures.